Analisis Pengendalian Piutang pada PT. DEF di Gresik - Ririn Nur Aini Safitri; Anita Handayani (Jurnal Simki Economic, 2025)
PT. DEF is a construction services company that implements cash and credit sales. In credit sales will generate receivables as a result. This research is motivated by the high number of bad debts in the company, which has a negative impact on cash flow and profitability. The purpose of this study is to identify the factors that cause bad debts and to evaluate the accounts receivable control system implemented by PT. This research uses a qualitative method with a case study approach. The types of data used are primary data and secondary data. Data collection techniques through observation, interviews, and documentation. The results showed that uncollectible receivables at PT. DEF were caused by a lack of assessment of the debtor's eligibility, the debtor's business failure and the debtor's bad intention not to repay the debt. This research concludes that PT. DEF needs to strengthen the assessment of debtors' creditworthiness regarding their payment history and financial ability to repay their debts.